Effects of nitrite on the abatement efficiency of 17a-ethinylestradiol during treatment of synthetic municipal wastewater effluent with UV and UV/H2O2 - Narvato, Kathleen Jane F.; De Luna, Mark Daniel G.; Lee, Yunho (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
17a-Ethinylestradiol or EE2 is one of the emerging contaminants (also known as micropollutants) that can cause adverse effects on aquatic organisms, even at very low concentrations, via interactions with the endocrine system. Its source is primarily due to the widespread use of oral contraceptives. Only fraction of these micropollutants can be removed in a conventional wastewater treatment system, thus enhanced wastewater treatment technologies such as advanced oxidation processes (AOPs) have been studied in the past years. Examples of these AOPs are ozonation, photo-Fenton processes, UV photolysis or UV photocatalysis. In this study, bench-scale experiments were conducted to examine the effect of nitrite on the abatement efficiency of EE2 in synthetic wastewater effluent matrices during UV (254 nm) and UV/H2O2 treatment. The degradation of EE2 followed pseudo first-order kinetics with UV fluence. The degradation rate of EE2 was higher in UV/H2O2 as compared to UV alone. In UV/H2O2 treatment (pH 7), the EE2 degradation rate decreased with increasing nitrite concentration. This was in contrast with alkaline conditions (i.e. pH 8.5 and pH 10) in which the EE2 degradation rate increased at higher nitrite concentration. These behaviors could be explained by the scavenging of OH by nitrite forming NO2 and the subsequent reaction of NO2 with EE2 with increasing rate at higher pH. Nitrite was oxidized to nitrate to some extent via NO2 as the primary intermediate.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Ethinyl estradiol; Sewage -- Purification -- Oxidation